Respuesta :

Hello from MrBillDoesMath!

Answer:

x = 4, y = 5

Discussion:

-2x + 5y = 17          (*)

x     +  y  = 9            (**)

Multiplying (**) by 2 gives

2x + 2y = 18            (***)

Adding (*) and (***) gives

(-2x + 5y) + (2x + 2y) = 17 + 18              =>

(-2x + 2x) + (5y + 2y)  =35                    => as -2x + 2x = 0 and 5y +2y = 7y

0 + 7y = 35                                           => divide both sides by 7

y = 35/7 = 5

Substituting y = 5 in (**) gives x + y = 9 or x + 5 = 9 => x = 9-5 = 4

Thank you,

MrB